2021
DOI: 10.1007/s40843-021-1860-x
|View full text |Cite
|
Sign up to set email alerts
|

hcp-phased Ni nanoparticles with generic catalytic hydrogenation activities toward different functional groups

Abstract: Catalytic hydrogenation is a vital industrial means to produce value-added fuels and fine chemicals, however, requiring highly efficient catalysts, especially the nonprecious ones. To date, the majority of high-performance industrial hydrogenation catalysts are made of precious metals-based materials, and any given catalyst could only be used to catalyze one or few specific reactions. Herein, we exemplify a crystal phase engineering approach to empower Ni nanoparticles (NPs) with superb intrinsic catalytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The single-crystal-to-single-crystal (SCSC) conversion is an intriguing and essential process in chemistry and material science and is an important feature in the preparation of coordination polymers [132][133][134][135][136][137][138][139] . Over the last few decades, much research demonstrated that SCSC conversions of MOFs could be triggered by external stimuli, including physical and chemical processes, such as temperature, pressure, gas adsorption, etc.…”
Section: Phase Transition Methodsmentioning
confidence: 99%
“…The single-crystal-to-single-crystal (SCSC) conversion is an intriguing and essential process in chemistry and material science and is an important feature in the preparation of coordination polymers [132][133][134][135][136][137][138][139] . Over the last few decades, much research demonstrated that SCSC conversions of MOFs could be triggered by external stimuli, including physical and chemical processes, such as temperature, pressure, gas adsorption, etc.…”
Section: Phase Transition Methodsmentioning
confidence: 99%
“…42 The d% of Ni is 40, Lv et al prepared nanoscale hcp-phased Ni supported on carbon that exhibited outstanding hydrogenation catalytic activities in pure water towards nitro-, aldehyde-, ketone-, alkene-and N heterocycliccompounds. 43 In addition, the particle size of the catalyst has different effects on different catalytic reactions. For some catalytic reactions, the best catalytic effect may be achieved within a certain particle size scale.…”
Section: Catalytic Role Of Single Metal Catalysts In Biomass Pyrolysismentioning
confidence: 99%
“…42 The d% of Ni is 40, Lv et al prepared nanoscale hcp-phased Ni supported on carbon that exhibited outstanding hydrogenation catalytic activities in pure water towards nitro-, aldehyde-, ketone-, alkene- and N heterocyclic-compounds. 43…”
Section: Catalytic Role Of Single Metal Catalysts In Biomass Pyrolysismentioning
confidence: 99%
“…Reducing the catalytic dehydrogenation barrier (the key rate-controlling step) is crucial for ethanol coupling under mild conditions. 27,28 The hexagonal-close-packed (hcp) Ni is quite active in de-/hydrogenation reactions due to its unique spatial arrangement and electronic structure compared to traditional face-centered-cubic (fcc) Ni, [29][30][31][32][33][34][35] but its fabrication is still challenging due to the thermodynamically metastable nature of hcp-Ni. 4,26,34,36,37 Herein, we developed a facile surfactant-induced carbonization strategy, which uses the amide-containing polymer polyvinylpyrrolidone (PVP) as an inducer and carbon source, to construct the thermostable hcp-Ni dominated hcp/fcc-Ni@C catalyst.…”
Section: Introductionmentioning
confidence: 99%